2014
DOI: 10.1007/s00264-013-2277-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological outcome of the Total Evolutive Shoulder System (TESS®) reverse shoulder arthroplasty: a prospective comparative non-randomised study

Abstract: Purpose The aims of this study were to assess the function and quality of life after the Total Evolutive Shoulder System (TESS) reverse shoulder arthroplasty (RSA), to evaluate the radiological stability of the stemless version and to address the effect of arm lengthening and scapular notching (SN) on the outcome. Methods This was a prospective comparative nonrandomised study. A total of 37 consecutive patients (40 shoulders) underwent TESS RSA between October 2007 and January 2012; 16 were stemless and 26 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 25 publications
6
41
0
Order By: Relevance
“…In our series one patient (132°humeral component) presented with a post-traumatic dislocation which was successfully treated with a higher liner and subscapularis reinsertion. This instability rate (4 %) is comparable with rates of previous reports for stemless RSA (0 %, 1 %, 2 %, and 13 %) [13][14][15][16], as well as the traditional Grammont design (4 %) [22].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…In our series one patient (132°humeral component) presented with a post-traumatic dislocation which was successfully treated with a higher liner and subscapularis reinsertion. This instability rate (4 %) is comparable with rates of previous reports for stemless RSA (0 %, 1 %, 2 %, and 13 %) [13][14][15][16], as well as the traditional Grammont design (4 %) [22].…”
Section: Discussionsupporting
confidence: 78%
“…No general loosening of the humeral component was noted in both groups, which confirms previous findings [13][14][15][16]. While in the RSA group with stem 29 % of the cases showed radiolucencies or visible bone density loss in one or two of eight zones, in none of the cases more than two zones were affected.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Raiss et al demonstrated a reduction in survivorship at 10 and 15 years after TSA performed with cement secondary to pain and implant loosening; revision procedures occurred at a mean of 8.8 years from the date of implantation 125 . The five RSA studies with minimum follow-up of 5 years noted scapular notching and instability as the most common complications 28 [33][34][35][36][37][38][39][44][45][46][47][48]50,51,53,54,[56][57][58][59]61,64,65,67,69,70,73,75,79,81,[88][89][90][91][92][93][94][95][96][97][98][99][100][101][102]104,105,…”
mentioning
confidence: 99%